2017
DOI: 10.4103/ijnmr.ijnmr_171_16
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the relationship between spiritual and social health and the self-care ability of elderly people referred to community health centers

Abstract: Background:Promotion of self-care ability among older people is an essential means to help maintain and improve their health. However, the role of spiritual and social health has not yet been considered in detail in the context of self-care ability among elderly. The aim of this study was to assess the relationship between spiritual and social health and self-care ability of older people referred to community health centers in Isfahan.Materials and Methods:In this cross-sectional correlation study, 200 people,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Spiritual knowledge and beliefs have been perceived as being influential in the caregivers' hopefulness and motivation to carrying out self-care activities. [ 32 ] Believing and trusting in god has been identified as a reliable power that can cure even incurable diseases. [ 27 ] Participants' experiences showed that sudden diagnosis of cancer, incomplete preparation for the role of care and uncertainty about the future cause cognitive and emotional problems in caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Spiritual knowledge and beliefs have been perceived as being influential in the caregivers' hopefulness and motivation to carrying out self-care activities. [ 32 ] Believing and trusting in god has been identified as a reliable power that can cure even incurable diseases. [ 27 ] Participants' experiences showed that sudden diagnosis of cancer, incomplete preparation for the role of care and uncertainty about the future cause cognitive and emotional problems in caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…45 Several studies have demonstrated that enhancing the spiritual dimension in one's life can enhance adaptability to changing circumstances, 46 promote the maintenance of mental health, 47 and improve social functioning. 48 Additionally, spirituality contributes to increased cognitive flexibility and individual resilience when faced with challenging situations. 49 The increasing family resilience is associated with higher degrees of spiritual well-being religious well-being and existential well-being.…”
Section: Discussionmentioning
confidence: 99%
“…These factors can threaten the quality of life (QoL) [6]. The literature shows that social health in older adults is related to social support [7], self-care behaviors [8], social adaptation, QoL [6], and the mortality of older adults [9,10]. Therefore, it is important to pay attention to the social health of older adults [11].…”
Section: Introductionmentioning
confidence: 99%